Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for CYP2D6 and Tamoxifen Therapy. Issue 5 (31st January 2018) - Goetz, Matthew P.; Sangkuhl, Katrin; Guchelaar, Henk‐Jan; Schwab, Matthias; Province, Michael; Whirl‐Carrillo, Michelle; Symmans, W. Fraser; McLeod, Howard L.; Ratain, Mark J.; Zembutsu, Hitoshi; Gaedigk, Andrea; van Schaik, Ron H.; et al.
Abstract : Tamoxifen is biotransformed by CYP2D6 to 4‐hydroxytamoxifen and 4‐hydroxy N‐desmethyl tamoxifen (endoxifen), both with greater antiestrogenic potency than the parent drug. Patients with certain CYP2D6 genetic polymorphisms and patients who receive strong CYP2D6 inhibitors exhibit lower endoxifen concentrations and a higher risk of disease recurrence in some studies of tamoxifen adjuvant therapy of early breast cancer. We summarize evidence from the literature and provide therapeutic recommendations for tamoxifen based on CYP2D6 genotype.